Purwarupa Pengendalian Jarak Jauh Pada Mobile Robot Berbasis Web Melalui Jaringan Wireless TCP/IP - Fajar Rinto Hadiputra; Tri Kuntoro Priyambodo (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2016)
It has been successfully developed a prototype mobile robot, controlled remotely, based on web via wireless TCP/IP network. This prototype mobile robot adopts tank's movement, equipped with a surveillance camera to acquire real time data on surrounding environment, a webcam is used by user. Since it is controlled remotely from a web based application on host computer via wireless TCP/IP network, it could do some telemetry in such environment, which harmful for human. It uses a wireless device for birectional communication, to transmit and receive data. While on debugging, wireless communication are took place directly without any obstacle (line of sight), between host computer and prototype mobile robot.